Acidified nitrite contributes to the antitumor effect of cold atmospheric plasma on melanoma cells - Zimmermann, Tom; Gebhardt, Lisa; Kreiß, Lucas; Schneider, Christin; Arndt, Stephanie; Karrer, Sigrid; Friedrich, Oliver; Fischer, Michael Jochen Marco; Boßerhoff, Anja Katrin (International Journal of Molecular Sciences, 2021)
Cold atmospheric plasma (CAP) is partially ionized gas near room temperature with previously reported antitumor effects. Despite extensive research and growing interest in this technol-ogy, active components and molecular mechanisms of CAP are not fully understood to date. We used Raman spectroscopy and colorimetric assays to determine elevated nitrite and nitrate levels after treatment with a MiniFlatPlaster CAP device. Previously, we demonstrated CAP-induced acidification. Cellular effects of nitrite and strong extracellular acidification were assessed using live-cell imaging of intracellular Ca2+ levels, cell viability analysis as well as quantification of p21 and DNA damage. We further characterized these observations by analyzing established molecular effects of CAP treatment. A synergistic effect of nitrite and acidification was found, leading to strong cytotoxicity in melanoma cells. Interestingly, protein nitration and membrane damage were absent after treatment with acidified nitrite, thereby challenging their contribution to CAP-induced cyto-toxicity. Further, phosphorylation of ERK1/2 was increased after treatment with both acidified ni-trite and indirect CAP. This study characterizes the impact of acidified nitrite on melanoma cells and supports the importance of RNS during CAP treatment. Further, it defines and evaluates im-portant molecular mechanisms that are involved in the cancer cell response to CAP.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Acidification; Acidified nitrite; Cold atmospheric plasma; Malignant melanoma; Membrane damage; Nitration; Nitrite